Peningkatan Literasi Keuangan dan Kepedulian Ekonomi Anak berbasis Pretend Play bagi Orang Tua - Akhmad Suyono; Nurhuda Nurhuda; Merlina Sari (Studi Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: The level of financial literacy of the Indonesian people is still relatively low, making it necessary for citizens to have an increase in financial literacy. This is especially so for children, because this consumptive behavior is starting to be imitated by children along with the increasing number of advertisements on TV and social media. This community service activity (PKM) aims to provide financial literacy assistance to young children by using the pretend play method which is very appropriate for the stages of early childhood development in order to increase the habit of saving money Methodology: This activity was carried out using mentoring and socialization methods as well as a grand launching of books and financial literacy media Result: The event ran smoothly and was full of appreciation from the participants who attended. The context of play makes children happy in learning activities which will have an impact on increasing children's interest in learning. So, with an increase in children's interest in learning, it is hoped that the child's initiative will emerge in carrying out activities related to what is being studied. Limitations: Teach children to love saving Contribution: Parents are able to understand how important financial literacy is for early childhood and know the pretend play learning method in teaching financial literacy to children. In addition, this assistance can increase efforts to like to save in early childhood